2021
DOI: 10.3390/su13052625
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Intrinsic Characteristics of Cementitious Materials on Biofouling in the Marine Environment

Abstract: Coastal marine ecosystems provide essential benefits and services to humanity, but many are rapidly degrading. Human activities are leading to significant land take along coastlines and to major changes in ecosystems. Ecological engineering tools capable of promoting large-scale restoration of coastal ecosystems are needed today in the face of intensifying climatic stress and human activities. Concrete is one of the materials most commonly used in the construction of coastal and marine infrastructure. Immersed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 137 publications
0
17
0
Order By: Relevance
“…Up to now, the main development in reef was focused on its design and on its capacity to supply habitat for different fish and animal size [11]. More recent studies showed that surface bioreceptivity of concrete can be obtained and enhanced by slight modification of concrete composition and surface texture for instance: this was confirmed by laboratory studies [12] but also in-situ measurements [13]. The development of a laboratory test for the bio-receptivity of concrete is crucial: this allows to screen a very large range of concrete composition and surface texture in controlled conditions without any extra cost required to carry out colonization follow up in marine environment.…”
Section: Introductionmentioning
confidence: 91%
“…Up to now, the main development in reef was focused on its design and on its capacity to supply habitat for different fish and animal size [11]. More recent studies showed that surface bioreceptivity of concrete can be obtained and enhanced by slight modification of concrete composition and surface texture for instance: this was confirmed by laboratory studies [12] but also in-situ measurements [13]. The development of a laboratory test for the bio-receptivity of concrete is crucial: this allows to screen a very large range of concrete composition and surface texture in controlled conditions without any extra cost required to carry out colonization follow up in marine environment.…”
Section: Introductionmentioning
confidence: 91%
“…As an important part of the ecosystem, soil is easily degraded by a series of manmade activities such as tourism development activities, trampling, garbage discharge, etc., which affects the growth and development of vegetation and may eventually lead to the degradation of soil and vegetation. It affects the entire tourism environment and is not conducive to the sustainable development of eco-tourism [39]. The quality of soil conditions has an important impact on the survival of the soil ecosystem, the plant ecosystem that grows on it, its animal communities, and soil microbial communities, while it also plays an important role in the health and stability of the tourism ecosystem.…”
Section: The Influence Of Physical and Chemical Indexes Of Soil Under Tourism Disturbance On Bacteriamentioning
confidence: 99%
“…As the colonization of cementitious material by microorganisms is an essential step for the adhesion of other organisms (Mieszkin, Callow, and Callow, 2013;Rajitha, Nancharaiah, and Venugopalan, 2020;Salta et al, 2013), the aim is to favor this colonization in order to reduce the ecological impact of the structure and consequently increase biodiversity, without impacting the structure's strength and durability. Then, additional studies are necessary to determine the different factors that can influence the colonization of cementitious materials in the marine environment, but the main parameters seem to be the water pH, the materials chemical composition, and surface roughness or topography (Grosseau et al, 2015;Hayek et al, 2020aHayek et al, , 2021McManus et al, 2018;Miller et al, 2009Miller et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%